Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1055/s-0028-1097262
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of the Flowers of Woodfordia fruticosa

Abstract: Key Word lndex:' Woodfordia fruticosa; O c t a c o s a n o l ; b-Sitosterol; Chrysophanol-8-0-p-D-glucopyranoside. ..The flowers of . Woodjordia-fruticosa The plant Woodfordia fruticosa (Lythrawere found to contain octacosanol, ,6-sito-ceae) possesses a number of medicinal prosterol and c h r~s o p h a n o~-8 -O -~-~-~~u c o p~r -perties El, 21. anoside. Flowers of Woodfordia jruticosa were Downloaded by: Universite Laval. Copyrighted material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Desai et al (1971) first demonstrated the presence of the common plant constituents octacosanol and ␤-sitosterol in the stems. These were subsequently reported from the flowers also (Chauhan et al, 1979a), with ␤-sitosterol encountered even in the leaves (Dan and Dan, 1984). The other non-phenolic constituents reported include the steroid sapogenin hecogenin (1, Fig.…”
Section: Chemical Constituentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Desai et al (1971) first demonstrated the presence of the common plant constituents octacosanol and ␤-sitosterol in the stems. These were subsequently reported from the flowers also (Chauhan et al, 1979a), with ␤-sitosterol encountered even in the leaves (Dan and Dan, 1984). The other non-phenolic constituents reported include the steroid sapogenin hecogenin (1, Fig.…”
Section: Chemical Constituentsmentioning
confidence: 87%
“…Besides the flavonoids or tannins, the phenolic constituents so far known to occur in the plant include gallic acid in leaves and stems (Kalidhar et al, 1981;Kadota et al, 1990), ellagic acid (4) in leaves and flowers (Nair et al, 1976), bergenin (a Cglycoside of gallic acid, 5a) and the new constituent norbergenin (5b) in stems (Kalidhar et al, 1981), chrysophanol-8-O-␤-dglucopyranoside (6) in flowers (Chauhan et al, 1979a), and the naphthaquinone pigment lawsone (7) in leaves (Saoji et al, 1972).…”
Section: Chemical Constituentsmentioning
confidence: 98%
“…(Das et al 2007). Octacosanol and β-sitosterol are present in stems, (Desai et al 1971) flowers (Chauhan et al 1979) and leaves (Dan and Dan 1984). It is also known for its several biological activities which include immunemodulatory activities (Kroes et al 1993) and it is also known for extensive use in the treatment of leucorrhea, otorrhoea and menorrhagia in females (Oudhia 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known for its several biological activities which include immunemodulatory activities (Kroes et al 1993) and it is also known for extensive use in the treatment of leucorrhea, otorrhoea and menorrhagia in females (Oudhia 2003). In Indian subcontinent, the bark, leaves and flowers are commercially used as ayurvedic medicines (Chadha 1976). The flowers are used in the fine tanning of soft leather (Ranganayaki and Ranganathan 1966;Saoji et al 1972), while the red dye produced from the flowers is used for fabric dyes or as an adjuvant/mordant (Dastur 1951;Watt 1972).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] Phytochemical studies of Woodfordia fruticosa can be ascribed for its important bioactive phytoconstituents such as flavonoids, sterols, anthraquinones, saponins and tannins. [15][16][17] Earlier studies indicates, that Woodfordia fruticosa possess important pharmacological activities including antipyretic, anti-inflammatory, 18 immunomodulatory, 19 etc. None of herbal origin drug posses combine effect as anti-asthmatic, and anti-tussive activity.…”
Section: Introductionmentioning
confidence: 99%